Donald Trumpâ€™s Protectionist Trade Policy from the Perspective of Economic Nationalism - Bimantara, Azza (Jurnal Hubungan Internasional, 2018)
This article aims to analyze American trade policy under Donald Trumpâ€™s administration. President Trump has imposed a set of tariffs and quotas for such imported agriculture and manufactured products. Such trade policies triggered many American trading partners, most notably China and NAFTA members, to take any retaliatory measures, starting trade war. Preliminary observation on this issue starts with two problematization. First, Trumpâ€™s trade policies failed to push his trade partners for their trade compliances despite of their higher relative export dependency on American market rather than on the contrary. Second, most of Trumpâ€™s â€œtrade belligerentsâ€ are democratic countries; it is another anomaly for established assumption about democratic peace theory which has stated that structures and norms held by democratic countries prevent them to engage conflictual relations in both political-security and economy. Further research has found that competitive trade structure US Government faced at some traded commodities put American trade interests at stake against other conflicting countries. In order to protect such interest, President Trump must deliver restrictive measuresâ€”tariffs and quotasâ€”in favor of domestic industries and market. Such behavior is justified by both President Trumpâ€™s view and tenet aboutthe construction of American nation and his political mobilization of popular far-right mass which also contribute to the discourse of contemporary American nationalism. The result is American economic nationalism which drives domestic political configuration to support President Trumpâ€™s political economic initiatives.